Effect of Corona Discharge Plasma Radiation on the Viability of True Shallot Seeds (Allium cepa L. var. aggregatum) - Imam Firmansyah; Erma Prihastanti; Sri Widodo Agung Suedy; Zaenul Muhlisin; Arif Surahman (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
TSS (True Shallot Seed) need to be developed to address the quality and quality of shallot seeds. The seeds, however, still has constraints on its viability and germination. The objective of this study was to investigate the effect of corona discharge plasma radiation on the viability of true shallot seeds. The research was conducted in March - April 2023 at the Plasma Laboratory, Faculty of Science and Mathematics, Diponegoro University, and the germination test experiments at the the Agricultural Technology Research and Assessment Installation (IP2TP Ungaran). The experiment was designed completely randomized with 6 treatments of radiation time consisting of P0 (without radiation), P1 (5 min), P2 (10 min), P3 (15 min), P4 (20 min), and P5 (25 min). All treatments were carried out with 5 replications. The collected data were processed using ANOVA and then continued with the DMRT test. The results showed that the corona plasma radiation treatment for 15-25 min affected the parameters of germination, germination rate, seed growth rate, vigor index, seed uniformity, and sprout length.  Keywords: Plasm, Radiation, Shallots, TSS.